Study of the validity of a combined potential model using the Hybrid Reverse Monte Carlo method in Fluoride glass system - Mesli, S.M.; Habchi, M.; Kotb, M.; Xu, H. (Condensed Matter Physics, 2013)
The choice of appropriate interaction models is among the major disadvantages of conventional methods such as Molecular Dynamics (MD) and Monte Carlo (MC) simulations. On the other hand, the so-called Reverse Monte Carlo (RMC) method, based on experimental data, can be applied without any interatomic and/or intermolecular interactions. The RMC results are accompanied by artificial satellite peaks. To remedy this problem, we use an extension of the RMC algorithm, which introduces an energy penalty term into the acceptance criteria. This method is referred to as the Hybrid Reverse Monte Carlo (HRMC) method. The idea of this paper is to test the validity of a combined potential model of coulomb and Lennard-Jones in a Fluoride glass system BaMnMF₇ (M = Fe,V) using HRMC method. The results show a good agreement between experimental and calculated characteristics, as well as a meaningful improvement in partial pair distribution functions (PDFs). We suggest that this model should be used in calculating the structural properties and in describing the average correlations between components of fluoride glass or a similar system. We also suggest that HRMC could be useful as a tool for testing the interaction potential models, as well